Sagot :
Answer:
not. sure..
u can correct if there is a mistake.. tnx
Step-by-step explanation:
1.12(2)+6
=24+6
=30
2.6(3)-2(3)(5)+5
=18-2(15)-5
=18-30-5
=18-25
=7
3. 7+2(7-10)
=7+2(-3)
=7-6
=1
Answer:
11. 12a + 6 ; if a = 2
12(2) + 6 = 30
12. 6a - 2ab + 5 ; when a = 3 and b = 5
6(3) - 2(3)(5) + 5 = -17
13. x + 2(x - 10) ; if x = 7
7 + 2(7 - 10) = 1
14. 12b (b + 2) ; if b = 2
12(2) (2 + 2) = 96
15. (30b + 12) + y ; when b = 5 and y = 7
(30(5) + 12) + 7 = 169
Step-by-step explanation:
11. 12a + 6
12(2) + 6
24 + 6 = 30
12. 6a - 2ab + 5
6(3) - 2(3)(5) + 5
18 - 30 + 5 = -17 (if MDAS rule will be followed) and -7 (if not)
13. x + 2(x - 10)
7 + 2(7 - 10)
7 + 2(-3)
7 + -6 = 1
14. 12b (b + 2)
12(2) (2 + 2)
24 (4) = 96
15. (30b + 12) + y
(30(5) + 12) + 7
(150 + 12) + 7
162 + 7 = 169